Cluster analysis reveals three main patterns of beliefs and intention with respect to SARS-CoV-2 vaccination in patients with autoimmune and inflammatory diseases. (13th May 2021) - Felten, Renaud; Dubois, Maxime; Ugarte-Gil, Manuel F; Chaudier, Aurore; Kawka, Lou; Bergier, Hugo; Costecalde, Charlotte; Pijnenburg, Luc; Fort, Jérémy; Chatelus, Emmanuel; Sordet, Christelle; Javier, Rose-Marie; et al.
Abstract: Introduction: Given the COVID-19 pandemic, it is crucial to understand the underlying behavioural determinants of SARS-CoV-2 vaccine hesitancy in patients with autoimmune or inflammatory rheumatic diseases (AIIRDs). We aimed to analyse patterns of beliefs and intention regarding SARS-CoV-2 vaccination in AIIRD patients, as a mean of identifying pragmatic actions that could be taken to increase vaccine coverage in this population. Methods: Data relating to 1258 AIIRD patients were analysed using univariate and multivariate logistic regression models, to identify variables associated independently with willingness to get vaccinated against SARS-CoV-2. Subsets of patients showing similar beliefs and intention about SARS-CoV-2 vaccination were characterized using cluster analysis. Results: Hierarchical cluster analysis identified three distinct clusters of AIIRD patients. Three predominant patient attitudes to SARS-COV-2 vaccination were identified: voluntary, hesitant and suspicious. While vaccine willingness differed significantly across the three clusters ( P < 0.0001), there was no significant difference regarding fear of getting COVID-19 ( P = 0.11), the presence of comorbidities ( P = 0.23), the use of glucocorticoids ( P = 0.21), or immunocompromised status ( P = 0.63). However, patients from cluster #2 (hesitant) and #3 (suspicious) were significantly more concerned about vaccination, the use of a new vaccine technology, lack of long-term data in relation to COVID-19 vaccination, and potential financial links with pharmaceutical companies (P < 0.0001 in all) than patients from cluster #1 (voluntary). Discussion: Importantly, the differences between clusters in terms of patient beliefs and intention was not related to the fear of getting COVID-19 or to any state of frailty, but was related to specific concerns about vaccination. This study may serve as a basis for improved communication and thus help increase COVID-19 vaccine coverage among AIIRD patients.